Analysis of Global Research Trends in Psychological Approaches and Behavioural Change to Waste Management - T, Adarsh; K P, Haneena Sulthana; CA, Sandhya Aravind (Westscience Press, 2025)
The integration of psychological perspectives into waste management research has gained significant momentum in recent decades, reflecting a growing emphasis on behaviour-driven solutions to environmental challenges. This bibliometric analysis aims to systematically map the scientific landscape at the intersection of psychological interventions and waste management from 1992 to 2024, highlighting trends, thematic evolution, and collaboration patterns. A total of 1927 records were retrieved from the Scopus and Web of Science databases and analysed using the Bibliometrix R-package. The study explores annual publication trends, core journal sources, influential authors, country-wise scientific production, and conceptual structures through keyword co-occurrence, factorial mapping, and thematic analysis. Findings reveal a steady increase in annual scientific production, with exponential growth post-2010 and a record peak in 2024, indicating rising academic and policy interest in pro-environmental behaviour. Core journals such as Sustainability, Journal of Cleaner Production, and Waste Management dominate the publication landscape, while geographic trends highlight China, the United Kingdom, and the United States as major contributors. Thematic evolution shows a transition from technical and region-specific issues to behaviourally informed, people-centered approaches, including constructs such as pro-environmental behavior, circular economy, and community engagement. Factorial analysis via MCA demonstrates a conceptual divide between theory-driven research (e.g., Theory of Planned Behavior, norms, policy) and empirically focused studies (e.g., surveys, behavior change, demographics), with central constructs like sustainability and attitude bridging these themes. This study consolidates the intellectual development of this interdisciplinary domain and offers strategic insights for future research in sustainable behaviour, environmental psychology, and global waste governance.